Screening of essential oils against Lecanicillium fungicola - Lee, Lundoi Tobias (2020)
The fungus Lecanicillium fungicola is the causative agent of dry bubble disease in white button mushroom (Agaricus bisporus), being responsible for economic losses. This pathogen causes spots and deformities in the mushrooms, making them unmarketable. Its control can be done with the use of fungicides, in addition to hygiene measures. However, in Brazil there is no approved pesticides for mushroom cultivation, which prevents its legal use. Because of this, and the need to avoid the use of pesticides, natural alternatives have been sought for the control of pests and diseases. Essential oils have proven antimicrobial action in several studies and, therefore, can be a good alternative for the control of L. fungicola in Brazil. Thus, the objective of this work was to evaluate the antifungal action of different essential oils and major compounds on the mycelial growth of L. fungicola. Therefore, 13 essential oils and nine major compounds were tested in vitro in order to evaluate the mycelial growth of the fungus. The medium diffusion method was used at 1 and 0,1% concentrations. Some oils and major components showed only partial inhibition, which varied from 62 to 97%, depending on the concentration (1 or 0.1%). However, most of them showed 100% inhibition of fungal growth in the two doses tested. Therefore, in vitro tests demonstrated a great potential of these compounds as agents of control of L. fungicola in the cultivation of A. bisporus.